PENERAPAN MEDIA KARTU RUMAH ADAT UNTUK MENGENALKAN LITERASI BUDAYA PADA ANAK PRASEKOLAH - Suci Indah Laksita; Triana Noor Edwina Dewayani Soeharto; Muhammad Wahyu Kuncoro; Ni Made Nindya Ayu Besthari (LPPM Universitas Nusa Mandiri, 2026)
Preschool children are in a crucial developmental stage that requires balanced stimulation of physical, cognitive, psychosocial, and language aspects to develop optimally. However, the low level of literacy in Indonesia, particularly cultural literacy among early childhood learners, highlights the need to strengthen literacy from the preschool level through engaging and culture-based learning methods to instill character values and preserve national culture. One approach that can be applied is the use of visual learning media suited to children’s developmental characteristics. This service activity aimed to examine the implementation of traditional house card media to introduce cultural literacy to preschool children at TBM Rumah Baca Bintang Sedayu, Bantul. The study employed a quantitative quasi-experimental method using a one-group pretest–posttest design. Participants consisted of 10 preschool children aged 5–6 years. The activity was conducted over approximately three months, including planning, implementation, and evaluation. The results showed that the total pretest score increased 26% on the posttest, with an average N-Gain score of 0.26 (low category) and a statistically significant improvement (Wilcoxon Signed Ranks Test, p = 0.006 < 0.05). Therefore, traditional house card media are effective in introducing cultural literacy to preschool children.